Farmers’ attitude towards modern maize production in Dinajpur Sadar upazila - Hossain, Md Belal; Mondol, Md Abu Sayed; Goswami, Pallab; Huda, Saiful (International Journal of Agricultural Research, Innovation and Technology, 2024)
The vital determination of the study was to determine the farmers’ attitudes towards modern maize production. The study was carried out in the Chehelgazi unions of Sadar upazila under Dinajpur District. Ninety-two farmers were selected as sample from an updated list of 920 farmers involved in maize production. Data were collected by a pre-tested interview schedule during September to October 2017. Simple and direct questions with different scales were used to obtain information. The co-efficient of correlation (r) was computed to explore the relationships between the nine selected characteristics of the farmers and their attitude towards modern maize production. About three-fourths (73.9%) of the farmers had highly favorable attitude towards modern maize production, while 26.1% moderately favorable attitude and none of them had slightly favorable attitude towards modern maize production. Correlation analyses indicated that among nine selected characteristics, education, farm size, cosmopoliteness, and extension media contact of the farmers had significant positive relationships with their attitude towards modern maize production. However, age, family size, area under maize production, annual income and training received had no significant relationships with their attitude towards modern maize production. ‘Cost of modern maize production is high than other crops’ (78.3%) emerged as the 1st ranked problem and last ranked (25.0%) perceived problem mentioned by the farmer was ‘Lack of knowledge on hybrid maize variety’ expressed by the farmers. The vital (56.5%) suggestion cited by the farmers was ‘organizing more training program for the farmers’ and ‘Application of IPM technique’ (28.3%) was last suggestion. Int. J. Agril. Res. Innov. Tech. 14(1): 96-103, June 2024